Cross Vision : How the Crucifixion of Jesus Makes Sense of Old Testament Violence - Boyd, Gregory A., 1957- (Book collections on Project MUSE., 2017)
The Old Testament God of wrath and violence versus the New Testament God of love and peace it's a difference that has troubled Christians since the first century. Now, with the sensitivity of a pastor and the intellect of a theologian, Gregory A. Boyd proposes the "cruciform hermeneutic," a way to read the Old Testament portraits of God through the lens of Jesus' crucifixion. In Cross Vision, Boyd follows up on his epic and groundbreaking study, The Crucifixion of the Warrior God. He shows how the death and resurrection of Jesus reframes the troubling violence of the Old Testament, how all of Scripture reveals God's self-sacrificial love, and, most importantly, how we can follow Jesus' example of peace.